Karl Barth's Epistle to the Romans Retrospect and Prospect - Chalamet, Christophe; Dettwiler, Andreas; Stewart-Kroeker, Sarah (Theologische Bibliothek Töpelmann, 2022)
This volume considers Karl Barth's first major publication, his commentary on the apostle Paul's epistle to the Romans in its two editions (1919 and 1922), analyzing both its contents and its relevance today. The volume includes essays by specialists of Barth's thought as well as by prominent contemporary thinkers who, sometimes for the first time, assess Barth's contribution.